Clinical features differentiating biliary atresia from other causes of neonatal cholestasis. - Lee, W.S.; Chai, P.F. (2010)
We did not find any single clinical feature with sufficient sensitivity and specificity to differentiate BA from other causes of NC. Repeated inspection of stools colour is necessary as occasionally, patients with BA may have initial pigmented stools. Biochemical assessment and imaging studies are important in the assessment of any infant with NC.